Nitrogen source and timing effect on carbohydrate status of bermudagrass and tall fescue - Goldsby, Anthony Lee (Kansas State University, 2008)
Non-structural carbohydrates (NSC) are important for plant health and recovery from stress. Controlled-release N sources may moderate turfgrass vegetative growth, thereby maximizing NSC levels. Three studies were conducted to determine the effect of N source/timing on NSC levels, turfgrass visual quality, and color of ‘Midlawn’ bermudagrass and turf-type tall fescue. Additionally, the effect on low temperature tolerance of bermudagrass and brown patch incidence on tall fescue was investigated. Nitrogen sources included two polymer-coated ureas (PCU), a polymer-sulfur coated urea (SCU) and urea formaldehyde (UF). Total annual N was applied in either late summer or spring for bermudagrass, and either late summer or split between late summer and spring for tall fescue. Urea, applied at traditional timings, was a control in all studies. NSC status was determined at regular intervals by extracting two cores from each plot, defoliating, and measuring regrowth in a dark growth chamber. Turfgrass color, visual quality and brown patch incidence were rated monthly during the growing season. Bermudagrass low temperature tolerance was evaluated by subjecting plugs to a freezing regime and evaluating regrowth. Over the 2-yr study, N source did not have a significant effect on bermudagrass or tall fescue NSC levels, color, or visual quality. Timing of application, by contrast, did have a significant impact. For bermudagrass, August-applied N resulted in higher overall NSC levels and improved fall color. For tall fescue, split Sept/March applications improved color; but split Sept/ May applications reduced NSC compared to a single Sept application. Brown patch incidence was unaffected by N source or timing, though disease pressure was low. Timing of PCU application did not affect low temperature tolerance of bermudagrass, but PCU improved low temperature survival compared to urea.
Keywords: Nitrogen; Fertilization; Winterkill; Bermudagrass; tall-fescue; Non-Structural Carbohydrates; Agriculture, Agronomy (0285)